Determinação de chumbo em tubos de raios catódicos e em solo contaminado por espectrometria de absorção atômica - Lima, Luiz Rogerio Monteiro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this paper methods for the determination of lead in glass from cathode ray tube (CRT) and soil pipes contaminated by this type of waste were employed. Small parts of components CRT (television and computer) from different manufacturers were used and dismantled manually for analysis. After grinding, the vitreous samples were analyzed by SEM, EDS and XRD to determine the particle size and the elemental composition of the investigated material. For this study a mixture ratio of 1:1:1:4 by weight (electron gun, neck, funnel and screen) was used. For the analyzes by atomic absorption spectrometry in graphite furnace (GFAAS) samples were digested in acid medium ( HCl 2,4 mL, 1,2 mL HNO 3 , 2,4 mL HF and 2,0 mL of H 2 O) where about 125 mg of the glassy sample was added in PTFE bottle from the quantification was performed using the method of addition of analyte. . The total concentration of lead in CRTs was determined by GFAAS and the value for two mixtures from different samples were 735, 52 ± 6, 12 mg.kg -1 and 886.61 ± 5, 49 mg.kg -1 . The toxicity of the sample was assessed using the norm ABNT NBR 10004:2004 solid waste. The mixture was subjected to leaching tests and the leaching extract was analyzed by optical emission spectrometry with inductively coupled plasma (ICP OES) and atomic absorption spectrometry in flames (FAAS). The results indicated that about 85% of Pb present in the leach residue. The leaching tests performed for waste CRTs reached values of Class I (hazardous waste) in compliance with norm ABNT NBR 10004:2004, due to the high concentration of lead present in their composition. The danger of the glass was determined using Toxicity Characteristic leashing Procedure ( TCLP ) ( SW- 846 Method 1311 , USEPA 2003) , which determines the toxicity of waste by leaching . Waste CRTs were used in the simulation of improper disposal in soil and lettuce cultivation in contaminated ...

No presente trabalho foram empregados métodos para a determinação de chumbo em vidros provenientes de tubos de raios catódicos (CRT) e solo contaminado por este tipo de resíduo. Para as análises foram utilizadas pequenas partes dos componentes do CRT (televisão e computador) de diferentes fabricantes e desmontadas manualmente. Após a moagem, as amostras vítreas foram analisadas por MEV, EDS e DRX para determinar o tamanho de partículas e a composição elementar do material investigado. Para este estudo foi utilizada uma mistura de proporção de 1:1:1:4 em peso (canhão de elétrons, pescoço, funil e tela). Para as análises por GFAAS as amostras foram digeridas em meio ácido (2,4 mL de HCl, 1,2 mL HNO 3 , 2,4 mL de HF e 2,0 mL de H 2 O), onde cerca 125mg da amostra vítrea foram adicionados em frasco de PTFE. A concentração total de chumbo nos CRTs foi determinada por GFAAS e os valores encontrados para duas misturas provenientes de diferentes amostras foram (735,52 ± 6,12) mg kg -1 e (886,61 ± 5,49) mg kg -1 . A toxicidade da amostra foi avaliada utilizando a norma ABNT NBR 10004:2004 para resíduos sólidos. A mistura foi submetida a ensaios de lixiviação e o extrato lixiviado foi analisado por espectrometria de absorção atômica em chama (FAAS) e espectrometria de emissão óptica com plasma indutivamente acoplado (ICP OES). Os resultados indicaram que cerca de 85% do Pb presente no resíduo foi lixiviado. Os testes lixiviação realizados para os resíduos de CRTs atingiram os valores de Classe I (resíduo perigoso) de acordo com a norma ABNT NBR 10004:2004, devido à alta concentração de chumbo presente em sua composição. Os resíduos dos CRTs foram utilizados na simulação de descarte inadequado no solo e cultivo de alface em ambiente contaminado, após a colheita foram coletadas amostras de solo e a alface. Foi realizada uma avaliação biométrica da alface para ...
Keywords: Solos - Teor de chumbo; Tubos de imagem de televisão; Raios catodicos; Lixiviação; Alface - Cultivo; Soild Lead content